Resistance to Plant-Parasitic Nematodes in Chickpea: Current Status and Future Perspectives - Zwart, Rebecca S.; Thudi, Mahendar; Channale, Sonal; Manchikatla, Praveen K.; Varshney, Rajeev K.; Thompson, John P. (Frontiers in Plant Science, 2019)
Plant-parasitic nematodes constrain chickpea (Cicer arietinum) production, with annual yield losses estimated to be 14% of total global production. Nematode species causing significant economic damage in chickpea include root-knot nematodes (Meloidogyne artiella, M. incognita, M. javanica), cyst nematode (Heterodera ciceri), and root-lesion nematode (Pratylenchus thornei). Reduced functionality of roots from nematode infestation leads to water stress and nutrient deficiency, which in turn lead to poor plant growth and reduced yield. Integration of resistant crops with appropriate agronomic practices is recognized as the safest and most practical, economic and effective control strategy for plant-parasitic nematodes. However, breeding for resistance to plant-parasitic nematodes has numerous challenges that originate from the narrow genetic diversity of the C. arietinum cultigen. While levels of resistance to M. artiella, H. ciceri and P. thornei have been identified in wild Cicer species that are superior to resistance levels in the C. arietinum cultigen, barriers to interspecific hybridization restrict the use of these crop wild relatives, as sources of nematode resistance. Wild Cicer species of the primary genepool, C. reticulatum and C. echinospermum, are the only species that have been used to introgress resistance genes into the C. arietinum cultigen. The availability of genomic resources, including genome sequence and re-sequence information, the chickpea reference set and mini-core collections, and new wild Cicer collections, provide unprecedented opportunities for chickpea improvement. This review surveys progress in the identification of novel genetic sources of nematode resistance in international germplasm collections and recommends genome-assisted breeding strategies to accelerate introgression of nematode resistance into elite chickpea cultivars.